Synthesis and characterization of sulfur nanoparticles with WSP/surfactants mixtures (International Journal of Biology and Chemistry, 2019)
Sulfur nanoparticles display unique physical and chemical feature because of effects such as the quantum size effect, mini size effect, surface effect, and macro-quantum tunnel effect. Therefore, sulfur nanoparticles would present higher efficacies such as removal of heavy metals, radical-scavenging, antimicrobial activity, antioxidant and antitumor activities. They have been using as a fungicide product in agriculture and medicine; to obtain sulfur fertilizers and cosmetics industries, as well as in obtaining nanocomposite lithium batteries; to form stable carbon chains such as C3S and C5S for obtaining hybrid materials with useful properties for gas sensor and catalytic applications. This work presents the results of obtaining sulfur nanoparticles, which can be used in agriculture as a fungicide treatment. Sulfur nanoparticles were obtained by modifying the surface of sulfur by various water-soluble polyelectrolyte (WSP)/surfactant mixtures including NaCMC/CTAB, PDADMAC/SDBS, NaCMC/Triton X-100 (TX-100). The size and the structure of sulfur nanoparticles were determined by methods as LSA, XRD, SEM. It is shown that the nanoparticles have a sulfur monoclinic α-form, and their average size is in the range of 100-300 nm. The received products can be considered as perspective forms of application in agriculture and medicine.